Through the looking glass - "Carroll, Lewis" (Puffin Books, London, 1994)
When Alice steps through the looking-glass, she enters a world of chess pieces and nursery rhyme characters who behave very strangely. Humpty Dumpty, Tweedledee and Tweedledum, the dotty White Knight and the sharp-tempered Red Queen - none of them are what they seem. In fact, through the looking-glass, everything is distorted.
Keywords: Fiction